The relationship between creb1 gene polymorphism and cardiac pathologies in pediatric patients with down syndrome - Kargun, Kursat; Tuylu, Berrin Ayaz; Senol, Sefa (Parlar Scientific Publications, 2019)
This study aims to investigate the possible rela- tionship between the cyclic adenosine 3',5'-mono- phosphate (cAMP)-responsive element binding pro- tein-1 (CREB1) gene polymorphism and cardiac pathologies in pediatric patients with Down syndrome. Between March 2011 and June 2014, a total of 100 patients (42 males, 58 females; mean age: 3.19±3.79 years; range, 1 month to 10 years) with Down syndrome and 100 healthy controls (males, 46 females; 54 mean age: 6.43±5.27 years; range, 1 to 10 years), as assessed by echocardiography, who were admitted to pediatric cardiology clinic were included. CREB1 gene polymorphisms were determined with real-time polymerase chain reaction method. There was a statistically significant difference in the genotype and allele frequencies of rs4675690, rs2551640, rs10932201, rs2709376, and rs7594560 domains of CREB1 gene polymorphisms between the patient and control groups (p<0.05). However, there was no statistically significant difference in the genotype and allele frequencies of rs2254137, rs7569963, rs6740584, rs2551645, and rs2709377 domains of CREB1 gene polymorphisms between the patient and control groups (p>0.05). A statistically significant association was observed only between rs4675690 domain of CREB1 gene polymorphism and atrial septal defect (p<0.05). Our study results suggest that analysis of rs4675690 domain of CREB1 gene polymorphism may yield data on the risk for certain congenital heart diseases, such as atrial septal defect in patients with Down syndrome. © by PSP.
Keywords: CREB1; Down syndrome; Gene polymorphism; Pediatric